2016
DOI: 10.5897/jvmah2015.0422
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and drug resistance patterns of methicillin resistant Staphylococcus aureus from mastitic cows milk from selected dairy farms in and around Kombolcha, Ethiopia

Abstract: A cross sectional study was conducted between January and May 2015 in and around Kombolcha town, Eastern Amhara, to identify methicillin resistant Staphylococcus aureus and their resistance to antimicrobials and also to identify risk factors associated with the occurrence of dairy cow mastitis. A total of 150 dairy cows were included during the study period. A total of 600 quarters were examined to detect clinical and subclinical mastitis by physical examinations of udder and milk and California mastitis test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
8
22
2
Order By: Relevance
“…The antimicrobial sensitivity test results of the current CoPS isolates was almost in agreement with the findings of Asmelash et al [ 34 ] who reported 100% resistant to penicillin G and amoxicillin and 42.7% to cefoxitin; Abera et al [ 33 ] who reported 94.4% resistant to penicillin G and 58.3% to trimethoprim-sulfamethoxazole; Rgbe et al [ 29 ] who reported 82.4% of resistant to ampicillin and 52.9% to trimethoprim-sulfamethoxazole; Abebe et al [ 47 ] who observed 92.2% resistant to penicillin G and 33.3% to oxacillin; Abo-Shama [ 62 ] in Sohag Governorate, Egypt, who reported 43.1% resistant to oxacillin and 83.7% to one or more antimicrobial agent; Mueena et al [ 53 ] who reported 100% resistant to penicillin and amoxicillin; Fitsum [ 40 ] who reported 93.3% resistant to penicillin G, 53.3% to streptomycin, and 40% to tetracycline; Tilahun et al [ 35 ] who observed 100% resistant to penicillin G and amoxicillin and 42.7% to cefoxitin; Muyiwa et al [ 41 ] who illustrated a large proportion (60%–100%) of resistant to penicillin G, ampicillin, and streptomycin; Ananya and Pranab [ 56 ] who reported 87.5% resistant to penicillin G; Pati and Reena [ 31 ] who reported 96% resistant to penicillin G and 93% to ampicillin; and Jibril and Huruma [ 60 ] who reported 71.74% of resistant to penicillin G and 41.30% to tetracycline.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The antimicrobial sensitivity test results of the current CoPS isolates was almost in agreement with the findings of Asmelash et al [ 34 ] who reported 100% resistant to penicillin G and amoxicillin and 42.7% to cefoxitin; Abera et al [ 33 ] who reported 94.4% resistant to penicillin G and 58.3% to trimethoprim-sulfamethoxazole; Rgbe et al [ 29 ] who reported 82.4% of resistant to ampicillin and 52.9% to trimethoprim-sulfamethoxazole; Abebe et al [ 47 ] who observed 92.2% resistant to penicillin G and 33.3% to oxacillin; Abo-Shama [ 62 ] in Sohag Governorate, Egypt, who reported 43.1% resistant to oxacillin and 83.7% to one or more antimicrobial agent; Mueena et al [ 53 ] who reported 100% resistant to penicillin and amoxicillin; Fitsum [ 40 ] who reported 93.3% resistant to penicillin G, 53.3% to streptomycin, and 40% to tetracycline; Tilahun et al [ 35 ] who observed 100% resistant to penicillin G and amoxicillin and 42.7% to cefoxitin; Muyiwa et al [ 41 ] who illustrated a large proportion (60%–100%) of resistant to penicillin G, ampicillin, and streptomycin; Ananya and Pranab [ 56 ] who reported 87.5% resistant to penicillin G; Pati and Reena [ 31 ] who reported 96% resistant to penicillin G and 93% to ampicillin; and Jibril and Huruma [ 60 ] who reported 71.74% of resistant to penicillin G and 41.30% to tetracycline.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was more or less in line with the reports of Molalegne et al [ 25 ] in Bahir Dar and its environs, Ethiopia (28.8%), Mulugeta and Wassie [ 26 ] in and around Wolaita Sodo, Ethiopia (29.5%), and Bekele et al [ 27 ] in Hawassa Town, Ethiopia (34.3%). However, it was lower than the reports of Indu and Brintya [ 28 ] in Silchar Town Dairy Farms, North East India (35.83%), Rgbe et al [ 29 ] in Northern Ethiopia (37.4%), Biniam et al [ 30 ] in and around Wolaita Sodo, Southern Ethiopia (40.9%), Pati and Reena [ 31 ] from Northern Plains of India (42.76%), Anueyiagu and Isiyaku [ 32 ] in Plateau State, Nigeria (43.75%), Abera et al [ 33 ] in Adama Town, Ethiopia (46.7%), Asmelash et al [ 34 ] in and around Kombolcha, Ethiopia (56%), Tilahun et al [ 35 ] in and around Kombolcha Town, Eastern Amhara, Ethiopia (56%), and Shimels et al [ 36 ] in the Selale/Fitche area, North Showa, Ethiopia (83.1%). The differences in the prevalence of bovine mastitis might be due to the fact that mastitis is a complex disease and associated with different risk factors such as husbandry and management systems of the farms, difference in drug usages and/or treatment, and the geographical locations of the study sites.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antibiogram test, the PCR amplification result indicated that all antimicrobial tested CoPS isolates carried the fem A gene and among these isolates, 12 (37.5%) carried mec A gene (MRSA). This finding was in line with the findings of authors [70] [38], who reported 86.04% resistance to Penicillin G and 74.42% to Ampicillin [45], who reported 100% resistance to Penicillin G and 46.8% to Oxacillin, and 44.6% to vancomycin, detected mec A by polymerase chain reaction in 4 of the 18 MRSA isolates, and 88.9% multi-drug resistance [46], who reported 100% of resistance to Penicillin G, 65% to Amoxicillin, and 40% to Oxacillin [56], who reported 98.5% resistance to Penicillin G [55], who reported 95.3% resistance to Penicillin G, and 100% of multidrug resistance, and [52] who reported 95.5% resistance to Penicillin G and 95.5% of multidrug resistance. However, the current finding of MRSA was higher than the reports of [66] (8.93%) [38], (13.95%) [47], (8.3%) [45], (4.8%), and [73] (5.9%).…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Asmelash et al (2016) reported a high prevalence rate of S. aureus in clinical more than subclinical mastitis. However, other studies have proved that S.aureus is the main causative agent of subclinical mastitis (Gitau et al, 2014;Legesse et al, 2015).…”
Section: Discussionmentioning
confidence: 95%